Intestinal dysbiosis and its associations in chronic diseases in children (Research, Society and Development, 2024)
The human body is colonized by a variety of microorganisms essential for physiological functions, whose imbalance can result in intestinal dysbiosis, particularly significant in the gastrointestinal tract. During the first years of life, children undergo important changes in their intestinal microbiome. Chronic diseases, such as obesity and diabetes, affect both adults and children and may be associated with dysbiosis. In this integrative literature review of the literature, conducted in bibliographic repositories such as VHL, Medline and Lilacs, the objective was to identify studies that relate intestinal dysbiosis, in children, with chronic diseases, with an emphasis on prevalence and main impacts. The results highlight that dysbiosis is correlated with gastrointestinal symptoms in children with chronic diseases, with the diagnosis based on clinical signs. Factors such as malabsorption, laxative abuse and inadequate diet contribute to microbiome imbalance. Optimal treatment begins with dietary changes, such as glutamine supplementation, and may involve the use of specific probiotics and antibiotics, highlighting the importance of an integrated approach to managing gut health and preventing chronic disease. Therefore, it is concluded that the studies reviewed demonstrate that the intestinal microbiome plays a crucial role in the development and progression of several pediatric conditions, such as IBD, T1D, CD, respiratory and liver diseases, functional constipation and CF, highlighting the importance of intestinal dysbiosis and the therapeutic potential of probiotics, in addition to highlighting the need for more research to identify effective therapeutic and dietary strategies to improve children's health.